2021
DOI: 10.22349/1994-6716-2021-106-2-66-73
|View full text |Cite
|
Sign up to set email alerts
|

Research of the process of synthesis and properties of the obtained metal-matrix composite powders of the Ti/tib<sub>2</sub> system

Abstract: The paper proposes a method for preparing composite powders of the Ti/TiB2 system, studies the properties of the obtained composite powders, and also shows a series of experiments on its microplasma spraying. The properties of the sprayed coatings were investigated. On its basis the optimal ratio of the matrix and reinforcing components was established in order to increase significantly the hardness of the sprayed coatings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In samples of synthesized powders with a contents of titanium diboride 20% and 30%, an exothermic peak is observed in the right section of the DSC-curve. As a result of the thermogravimetric analysis, it can be concluded that the appearance of titanium dioxide phase, which was determined in early work [12], was formed in the process of homogenized Ti/TiB 2 powders synthesizing by the volumetric reinforcement, when using a vibration-band bowl. The synthesis takes place in the bowls with internal working bodies in which the source material and air are present.…”
Section: Resultsmentioning
confidence: 95%
“…In samples of synthesized powders with a contents of titanium diboride 20% and 30%, an exothermic peak is observed in the right section of the DSC-curve. As a result of the thermogravimetric analysis, it can be concluded that the appearance of titanium dioxide phase, which was determined in early work [12], was formed in the process of homogenized Ti/TiB 2 powders synthesizing by the volumetric reinforcement, when using a vibration-band bowl. The synthesis takes place in the bowls with internal working bodies in which the source material and air are present.…”
Section: Resultsmentioning
confidence: 95%
“…). The preservation of titanium diboride particles during the deposition process and their presence in the coating leads to an effective increase in operational properties compared to traditional titanium coating [20].…”
Section: Research Resultsmentioning
confidence: 99%
“…Microsections of the coating made of composite powder (30%) № 3, a) the transverse section of the coating (20 µm), b) the transverse sections of the coating (2 µm). The preservation of titanium diboride particles during the deposition process and their presence in the coating leads to an effective increase in operational properties compared to traditional titanium coating[20].The phase composition was studied from the surfaces of composite powders pressed into the cuvette and planar samples of sprayed coatings. A characteristic diffractogram of a composite powder of the Ti/TiB 2 system is shown in Figure5as the example of a composite powder with 20% titanium diboride.…”
mentioning
confidence: 99%